Evaluación de riesgos ergonómicos en profesionales sanitarios de un dispensario Tipo C en Latacunga-Ecuador - Ayala Pilco, Stefany Selene (2024)
Ergonomic risks are associated with working conditions related to postures, movements and the physical environment. With the objective of evaluating the level of ergonomic risks in health professionals of a type C dispensary in Latacunga-Ecuador. Based on the analysis of 91 workers from the aforementioned health center, with observation and records of work conditions on ergonomic risks present, using a standardized Nordic questionnaire for the perception of musculoskeletal symptoms. In addition, the REBA method is used to evaluate the degree of exposure of the worker to risk due to the adoption of inappropriate postures. As results, musculoskeletal symptoms were identified at the level of the neck, shoulders, lower back and knees; such findings with a higher proportion and high level of risk in the area of physiotherapy, dentistry and admission. Being rest and active breaks in the activities carried out, the preventive measures to implement